Influence of pH and antibiotic solubility on the removal of ciprofloxacin from aqueous media using montmorillonite - Roca Jalil, María Eugenia (2015)
The ciprofloxacin (CPX) is a fluoroquinolone antibiotic that has been found in soils and aqueous media due to its vast use in both, human and veterinary health care. As a consequence the removal of this kind of compounds is widely studied. However, there are a few studies about the CPX removal from aqueous media by adsorption.This work is focused on the study of CPX removal by adsorption using an Argentinian montmorillonite (Mt). The influence of the pH media and the consequent antibiotic solubility in the adsorption process was analyzed. The experimental curve of CPX solubility versus pH media showed a strong correlation between them where the lowest value of solubility was obtained for the zwitterion species (CPX±). This result points out the fact that the solubility of the CPX species must be considered in adsorption experiments because of the antibiotic precipitation and the consequent overestimation of the adsorbent adsorption capacities. CPX adsorption kinetics and adsorption isotherms at different pH values showed that the adsorption processes obey pseudo-second order kinetics. The CPX adsorption capacity of the Mt, the affinity of the species towards its surface and the possible mechanisms involved in the adsorption process were assessed by Langmuir, Freundlich and Scatchard methods. The results showed that the adsorption mechanism of CPX on Mt is pH dependent, obtaining a negative cooperative mechanism at pH3, 6 and 7.5 and a positive cooperative mechanism at pH10. The highest CPX adsorption capacity on Mt was obtained at pH6. Infrared spectroscopy and X-ray diffractograms of the complexes obtained after the adsorption process provided information about the interaction between the functional groups of CPX and the adsorption sites on Mt and the changes in the basal space related with the molecular arrangements of the CPX on the sample, respectively. The CPX removal by this clay mineral is remarkably higher when it is compared with other materials and quite similar to previous data obtained with other bentonites.